2008
DOI: 10.1128/jb.01406-07
|View full text |Cite
|
Sign up to set email alerts
|

TheXanthomonas oryzaepv. oryzae PhoPQ Two-Component System Is Required for AvrXA21 Activity,hrpGExpression, and Virulence

Abstract: The rice pathogen recognition receptor, XA21, confers resistance to Xanthomonas oryzae pv. oryzae strains producing the type one system-secreted molecule, AvrXA21. X. oryzae pv. oryzae requires a regulatory twocomponent system (TCS) called RaxRH to regulate expression of eight rax (required for AvrXA21 activity) genes and to sense population cell density. To identify other key components in this critical regulatory circuit, we assayed proteins expressed in a raxR gene knockout strain. This survey led to the id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(95 citation statements)
references
References 84 publications
(94 reference statements)
1
92
0
2
Order By: Relevance
“…The role of divalent cations as signals for PhoQ is also supported by the crystal structures of the PhoQ periplasmic sensor domains from S. typhimurium and E. coli [48]. Similarly, we have shown that the Xoo PhoPQ system is required for sensing low extracellular Mg 2+ and Ca 2+ concentrations, conditions that the pathogen likely is confronted with upon entry into the xylem of the rice plant [33]. In addition, we have shown that Ax21 activity is impaired in a phoQ knockout strain (PXO99DphoQ) as reflected by enhanced growth of this strain in rice lines carrying XA21 [33].…”
Section: Ax21 Is Predicted To Be An Inducer Of Densitydependent Gene mentioning
confidence: 59%
See 2 more Smart Citations
“…The role of divalent cations as signals for PhoQ is also supported by the crystal structures of the PhoQ periplasmic sensor domains from S. typhimurium and E. coli [48]. Similarly, we have shown that the Xoo PhoPQ system is required for sensing low extracellular Mg 2+ and Ca 2+ concentrations, conditions that the pathogen likely is confronted with upon entry into the xylem of the rice plant [33]. In addition, we have shown that Ax21 activity is impaired in a phoQ knockout strain (PXO99DphoQ) as reflected by enhanced growth of this strain in rice lines carrying XA21 [33].…”
Section: Ax21 Is Predicted To Be An Inducer Of Densitydependent Gene mentioning
confidence: 59%
“…RaxR is a substrate for RaxH trans-phosphorylation [32]. We demonstrated that the Xoo phoP gene, which encodes a response regulator, is up-regulated in the raxR knockout (PXO99DraxR) strain [33].…”
Section: Wwwsciencedirectcommentioning
confidence: 93%
See 1 more Smart Citation
“…PhoPPhoQ of X. oryzae pv. oryzae (Xoo), E. carotovora, and E. chrysanthemi appears to be cell density-dependent in plant host [4][5][6][7][8][9][10]. In this study, while both wild type and popP mutant X. fastidiosa strains showed similar growth curves in vitro, grapevines infected with popP deletion strain have significantly decreased bacterial populations in comparison to the bacterial populations of grapevines inoculated with wild type.…”
Section: Discussionmentioning
confidence: 74%
“…In phytopathogenic Xanthomonas oryzae pv. oryzae, TCS PhoP-PhoQ was recently shown to be a requirement for the induction of density-dependent gene expression, including genes related with biofilm formation [4][5][6][7]. PhoP-PhoQ controls virulence functions in the plant pathogen Erwinia carotovora and E. chrysanthemi [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%